Effect of long-term embryo cryopreservation on subsequent frozen embryo transfer outcomes: A retrospective cohort study - Nallamilli Sujatha Reddy; Chinta Parimala; Reka Karuppusami; Ann Margret Mangalraj; Aleyamma Thaiparambil Kunjummen (Wolters Kluwer Medknow Publications, 2022)
Background: The duration of cryopreservation of embryos and its effect on the subsequent pregnancy outcomes, when they have been frozen for a longer duration remains a matter of concern. There is a continuous debate among studies comparing different durations of embryo cryopreservation as the results are contradictory. Aims: This study aims to find out if long-term cryopreservation of embryos has any effect on pregnancy and perinatal outcomes. Settings and Design: Retrospective cohort study was conducted in the department of reproductive medicine and surgery in a university-level teaching hospital. Materials and Methods: The study included women who underwent frozen embryo transfer (FET) from autologous in vitro fertilisation between January 2012 and December 2020 with the duration of cryopreservation of more than 5 years as one group and 3-5 years as another group. Pregnancy and perinatal outcomes were analysed. Statistical Analysis Used: Regression analysis was performed using logistic regression by entering clinically important variables associated with pregnancy outcome, and the results were expressed as odds ratio with a 95% confidence interval (CI). All statistical analysis was performed with SPSS (version 21.0, IBM, USA). Results: A total of 1680 FET cycles were carried out during the study period. Among these, 75 cycles with a duration of 3-5 years and 20 cycles with a duration of more than 5 years were included. Live birth rate (LBR) was 40.8% in the 3-5 years group and 35% in the more than 5 years group. After adjusting for important confounders, the LBR has no significant association in the more than 5 years group (adjusted odds ratio 1.07; 95% CI 0.34-3.32; P = 0.913) compared to the 3-5 years group. Conclusion: The duration of cryopreservation of embryos has no statistically significant effect on the pregnancy and perinatal outcomes.